2023
DOI: 10.1038/s41467-023-37943-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance of perovskite quantum dots dependent on A-site cation and surface ligand

Abstract: A detailed picture of temperature dependent behavior of CsxFA1-xPbI3 perovskite quantum dots across the composition range is constructed by performing in situ optical spectroscopic and structural measurements, supported by theoretical calculations that focus on the relation between A-site chemical composition and surface ligand binding. The thermal degradation mechanism depends not only on the exact chemical composition, but also on the ligand binding energy. The thermal degradation of Cs-rich perovskite quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…34 The intermixing degree should depend on the interaction between the two sizes of PQDs in terms of different surface energy as well as ligand densities and distributions. 10,35 Computer Modeling of the Influence of Organic Ligands on PQD Packing. While the trend of binarycomponent volume fraction shown in Table 1 agrees with the theoretical prediction on binary mixing, 26 the fitted volume fraction values are much lower than those predicted for random close packing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The intermixing degree should depend on the interaction between the two sizes of PQDs in terms of different surface energy as well as ligand densities and distributions. 10,35 Computer Modeling of the Influence of Organic Ligands on PQD Packing. While the trend of binarycomponent volume fraction shown in Table 1 agrees with the theoretical prediction on binary mixing, 26 the fitted volume fraction values are much lower than those predicted for random close packing.…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to polymers, the mixing of the two-sizes of PQDs may also lead to the formation of three phases–two monosized phases and one binary-mixing phase . The intermixing degree should depend on the interaction between the two sizes of PQDs in terms of different surface energy as well as ligand densities and distributions. , …”
Section: Resultsmentioning
confidence: 99%
“…The results showed that hybrid organic-inorganic FA-rich perovskite QDs have better thermal stability than all-inorganic CsPbI 3 QDs. [114] Up till now, triple-cation perovskites (Cs/MA/FA) are the most promising in terms of stability against halide segregation. [115] For B-site cations, partial replacement of Pb 2+ cations with smaller metal ions (Sn 2+ , Zn 2+ , Co 2+ , Mn 2+ , etc.)…”
Section: Intrinsic Instability Of Perovskite and Strain Effectmentioning
confidence: 99%
“…PQDs, despite their material benefits and excellent device performance, also inevitably come with some drawbacks. The high photoluminescence quantum yields (PLQY) and saturated color purity stem from their nanoscale size, but the huge specific surface area results in high surface energy. , Along with their soft lattice characteristics, external stimuli, such as water, heat, and photoirradiation, can remove or break their surrounding organic ligands. This effect can lead to the decomposition or aggregation of PQDs, significantly deteriorating their nanostructures and fluorescence performances.…”
Section: Introductionmentioning
confidence: 99%